1992
DOI: 10.1159/000154052
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-6-Phosphate Dehydrogenase Deficiency and Sickle Cell Disease in Brazil

Abstract: The frequency of glucose-6-phosphate dehydrogenase (G-6-PD) deficiency was determined in 54 male patients with sickle cell diseases: 31 sickle cell anemia (SS), 14 sickle cell hemoglobinopathyc (SC) and 9 HbS/β-thalassemia (S/B-thal) by a combination of quantitative assay, fluorescent spot test and electrophoresis. Of the 54 patients tested, 7 were found to be G-6-PD deficient (G-6-PD-) (3 SS, 3 SC and 1 S/B-thal) and 47 G-6-PD normal (G-6-PD+) (6 G-6-PD A and 41 G-6-PD B). All the deficient patients were G-6-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 10 publications
0
6
1
Order By: Relevance
“…[4][5][6]10,16 However the findings in the present study were contradictory to those of Carson and Frischer, Smits HL et al and Bouanga et al, in that a young red cell population associated with the sickle cell gene leading to elevated G6PD levels in G6PD deficient males suggests that sickle haemoglobin may exert a beneficial effect on G6PD deficiency, rather than the reverse. 1,7,17 These red cells may be better able to deal with oxidative stress (infection alone, drug alone, or a combination of both), which can precipitate severe haemolytic disease in G6PD deficiency.…”
Section: Severity Of Anemiacontrasting
confidence: 99%
See 1 more Smart Citation
“…[4][5][6]10,16 However the findings in the present study were contradictory to those of Carson and Frischer, Smits HL et al and Bouanga et al, in that a young red cell population associated with the sickle cell gene leading to elevated G6PD levels in G6PD deficient males suggests that sickle haemoglobin may exert a beneficial effect on G6PD deficiency, rather than the reverse. 1,7,17 These red cells may be better able to deal with oxidative stress (infection alone, drug alone, or a combination of both), which can precipitate severe haemolytic disease in G6PD deficiency.…”
Section: Severity Of Anemiacontrasting
confidence: 99%
“…et al, Steinberg MH et al and Saad STO et al too did not find any statistically significant difference in the reticulocyte count in sickle cell patients with and without G6PD deficiency. [4][5][6] Smits HL et al demonstrated a brisk reticulocytosis in patients with sickle cell disease and G6PD deficiency which was due to concurrent infection or administration of certain drugs known to cause hemolysis in G6PD deficient patients.…”
Section: Reticulocyte Countmentioning
confidence: 99%
“…27 Several investigators have found no difference in hemoglobin levels and sickled cells in patients with SCD with and without G6PD deficiency. 26,[28][29][30] Further study is needed to determine whether there is truly an association between G6PD deficiency and SR.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the exten sive racial mixture of this population, it was not possi ble to assert the exact origin of these blood donors. The 202 G-»A mutation was detected by allele specific oligomer hybridization, as described elsewhere [9], or digestion of the exon 4 of the G6PD gene with the restriction endonuclease MflIIl. The Mediterranean variant was detected by digestion of exon 6 with the restriction enzyme Mboll.…”
Section: Materials and M Ethodsmentioning
confidence: 99%